Assessing the Adherence to Insulin Therapy and the Effect of Injection Pain on Insulin Adherence among Type 2 Diabetes Mellitus Patients (Journal of Pharmaceutical Negative Results, 2020)
Background: Nearly all type 2 Diabetes Mellitus (DM) patients need eventual treatment with insulin at some point in their life. One of themajor problems that lead to failure of insulin therapy is lacking medication adherence, which is common among type 2 DM patients. Therefore,this study aimed to assess adherence to insulin therapy and the effect of insulin injection pain on insulin adherence among type 2 DM patients.Methodology: A cross-sectional pilot study was conducted on a convenient sample of 63 type 2 DM patients at the National Diabetes Center,Baghdad, Iraq, from November 2018 till March 2019. Adirect interview with each patient was conducted to assess the pain of injecting insulinthrough the use of a visual analog scale and to assess medication adherence using Medication Adherence Questionnaire, besides assessingpatient’s techniques to reduce the pain of injecting insulin. Results: The majority (81%) of the participants adhere to their insulin therapy;however, only a few (22.2%) of them adhere completely to their insulin therapy. There was a significant inverse correlation (R = −0.253;P = 0.045) between the degree of pain for injecting insulin with insulin adherence. In addition, the degree of pain reduced statisticallysignificantly (R = −0.346; P = 0.005) by practicing proper injecting techniques; however, the practice of these techniques can only modestlyimprove patient adherence to insulin therapy (R = 0.214; P = 0.092). Conclusion: Improper practice of insulin-injecting techniques can leadto a greater degree of pain and eventually reduce adherence to insulin therapy.